Exchange market pressure and domestic credit evidence from Poland - Bielecki, Szymon (Economics and Business Review, 2005)
Starting from the Girton-Roper definition of the exchange market pressure index (EMP) we use the index to describe the Polish exchange rate system in transition 1994-2002. We also compare EMP indices calculated under two alternative methodologies. For that purpose we use first all foreign reserve changes and then pure official FOREX intervention data, which seems to be more relevant for assessing the actual exchange market stance. In fact, it better catches 'events' in the history of the Polish currency market. However, the narrower index performs worse than the broader one in the estimated linear EMP models. On the contrary, in the case of a VAR model the EMP index based on the intervention data produces more clear and long-lived signals, confirming the strong sterilization practice by the Polish central bank in the first sample subperiod. (original abstract)